AN ANALYSIS OF GRAMMATICAL ERRORS MADE BY THE SEVENTH GRADE STUDENTS OF SMP NEGERI 2 SUKAWATI IN WRITING DESCRIPTIVE TEXTS IN THE ACADEMIC YEAR 2018/2019 - I.P.B. Erlangga; I.W. Suarnajaya; P.A.K. Juniarta (Universitas Pendidikan Ganesha, 2019)
This study aimed at describing the types of errors in seventh grade students’ descriptive texts and identifying causes of errors. There are two research questions in this study, namely: (1) What are types of grammatical errors made by seventh grade students of SMP Negeri 2 Sukawati in writing descriptive texts? and (2) What are the causes of grammatical errors made by seventh grade students of SMP Negeri 2 Sukawati in writing descriptive text?. The data for study were collected by document study, interview method, and recording. The instruments were researcher, writing task, guideline, interview guide, and mobile recorder. The results of this study showed that there were five types of errors found in students’ descriptive writing, namely: omission, addition, misformation, misordering, and spelling. The total number of errors was 541 errors. There were three causes error found in this study, namely: carelessness (40.67%), first language interference (53.42%), and translation (5.91%).